Potential for co-disposal and treatment of food waste with sewage: A plant-wide steady-state model evaluation - Iqbal, Asad; Ekama, George A.; Zan, Feixiang; Liu, Xiaoming; Chui, Ho-Kwong; Chen, Guang-Hao (Water research (Oxford), 2020)
•Plant-wide steady-state model was developed and tested for a case-specific WWTP.•Food waste disposal into sewers and bio-treatment with sewage is a viable option.•Food waste and sewage co-treatment has synergistic effect on WWTP's energy balance.•Net carbon footprint of treating per m3 sewage was reduced by ∼47%.•Energy self-sufficiency and greater resource recovery potential can be reached. The water, food and energy nexus is a vital subject to achieve sustainable development goals worldwide. Wastewater (WW) and food waste (FW) from municipal sources are the primary contributors of organic waste from cities. Along with the loss of these valuable natural resources, their treatment systems also consume a considerable amount of abiotic energy and resource input and make a perceptible contribution to global warming. Hence, the global paradigm has evolved from simple pollution mitigation to resource recovery systems. In this study, the prospects of FW co-disposal into the sewer system and treatment with municipal sewage were quantitatively investigated for Hong Kong's largest biological WW treatment plant (WWTP) by integrated plant-wide steady-state modelling (PWSSM) and lifecycle assessment (LCA) approaches. The investigation assessed the impacts on the design and operational capacity of the WWTP, effluent quality, sludge output, and its net energy and carbon footprint. The results revealed that even at a higher than normal FW to sewage ratio, the WWTP's organic load capacity and performance in terms of organics and nitrogen removal was not significantly degraded, in fact the denitrification efficiency was improved by the FW organics with low N/C ratio. The net energy balance was improved by 80-400%, the net carbon footprint was lowered by 37-63% (without biogenic emissions), while the sludge production was increased by ∼33%. The results are very sensitive and improved with greater influent FW concentration and solids capture in the primary settling unit of the WWTP. The differences in the results have to be seen in relation to uncontrolled methane emission and a faster filling rate if the FW were disposed to landfill. The study provides valuable insights and policy guidelines for the decision makers locally and a generic methodological template.